(untitled) (Journal of Informatics Education and Research, 2026)
The challenges inherent in the digital environment pose significant obstacles to the protection of digital works under existing legal regimes, particularly due to the inadequacy of statutory provisions in affording sufficient and effective safeguards for authors’ rights. This deficiency facilitates unauthorized exploitation of digital works without remuneration to the copyright holder, exacerbating concerns amid the evolution of piracy techniques and cyber infringements. In response, creators have increasingly resorted to technological protection measures (TPMs) as technical safeguards to secure their intellectual creations. This study illuminates the phenomenon of circumvention of technological protection measures by delineating their conditions, levels, and instruments that ensure the safeguarding of digital works embodying the author’s creativity. It further examines the legal framework prohibiting such circumvention.The research concludes with the necessity of amending Ordinance No. 03-05 to incorporate comprehensive provisions regulating technological protection measures. It also advocates for substantial investment in cybersecurity to render these measures robust against piracy, and calls for activating the role of the National Office of Copyright and Related Rights in protecting digital works.